Mediating role for metacognitive processes in the relationship between schizotypy and anxiety and depression symptoms. Issue 6 (2nd November 2022) - Webster, Lucy; Norman, Christine; Jones, Gary; Marriott, Mike
ABSTRACT: Introduction: Depression and anxiety symptoms are highly prevalent in schizophrenia-spectrum disorders and are commonly associated with schizotypy in non-clinical samples. However, it remains unclear what factors could be contributing to the relationships between schizotypy and anxiety and depression symptoms. Using path analysis, we explored the complex interplay between schizotypy, metacognitive beliefs, cognitive insight, and symptoms of emotional distress. Methods: Self-report data of schizotypy, metacognitive beliefs, cognitive insight, depression, and anxiety symptoms were collected from 344 participants from a predominantly student sample. Results: Path analysis confirmed unique associations between schizotypy dimensions, metacognitive beliefs, and cognitive insight. Furthermore, negative beliefs about worry mediated the link between the schizotypy dimensions, unusual experiences, cognitive disorganisation, and introvertive anhedonia and both depression and anxiety symptoms. Lack of cognitive confidence also mediated the relationship between cognitive disorganisation and depression symptoms. Finally, the cognitive insight subcomponent self-reflectiveness mediated the relationship between unusual experiences and cognitive disorganisation and anxiety. Conclusions: This study significantly furthers our understanding of the complex relationship between schizotypy, metacognitive processes, and emotional distress. Our findings also provide support for interventions which modify metacognitive beliefs and self-reflectiveness, which may prove beneficial for treatment in clinical settings.